The Contribution of Lexical Cohesion to the Text Cohesion in EFL Students’ Expository Texts - Hanif Nurcholish Adiantika (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2018)
The present study intends to investigate the use of substitution in students’ expository texts. It covers the types of substitution used by the students in their expository texts and the contribution of substitution to the texts’ cohesion. This study uses qualitative research through case study design. The participants in this study are nine students of twelfth grade in a public senior high school in Kuningan. The data in the present study are the documents of students’ expository texts. The data are analyzed by using the frameworks of cohesive devices proposed by Halliday and Hasan (1976). The findings indicate that there is only one substitution found in this study namely nominal substitution. The present study also delineates that the use of substitution contributes to the process of avoiding repetition and text redundancy. Furthermore, it can be concluded that the use and the contribution of substitution in students’ expository texts are still considered low. Thus, the encouragement is very necessary for the students to use appropriate substitution to make their texts more cohesive.